Predict and prevent microvascular complications of type 2 diabetes: a cross-sectional and longitudinal study in Chinese communities - Liu, Zhaoxiang; Zhou, Lianhao; Zhao, Wenhui; Jin, Lixia; Zhang, Jinping; Zhang, Yajing; Li, Yufeng; Deng, Guixia; He, Jiquan; Zhao, Xinghua; Zheng, Wenli; Tian, Yong; et al. (Frontiers in Endocrinology, 2025)
PurposeThis study investigates the incidence, predictors, and preventive strategies for microvascular complications in type 2 diabetes patients in community settings.MethodsData were collected from 3,008 type 2 diabetes patients enrolled across 31 clinics in Beijing and Hebei. Prevalence and incidence of diabetic kidney disease (DKD), diabetic retinopathy (DR), and diabetic peripheral neuropathy (DPN) were assessed. Predictors were identified using XGBoost and Cox regression, and the impact of lifestyle and multifactorial interventions (MFI) was analyzed.ResultsThe prevalence of DKD, DR, and DPN were 39.5%, 26.2%, and 27.1%, respectively, with incidences of 74, 21, and 28 per 1000-person year. XGBoost identified that diabetes duration, age, HbA1c, FBG, triglyceride, BP, serum creatinine, proteinuria, aspirin and statin use were associated with those microvascular complications. The risk of DKD increased more rapidly as HbA1c exceeded 7.5% and decreased as blood pressure was maintained below 120/70 mmHg. Cox regression models showed that community-based intervention, including lifestyle modifications, were associated with a lower risk of DR and DPN. The study also found that higher variability in HbA1c and albumin-to-creatinine ratio (ACR) was associated with an increased risk of microvascular complications.ConclusionsCommunity-based interventions significantly reduce the of DR and DPN, highlighting the need for individualized glycemic and BP management in primary care. The findings emphasize the importance of comprehensive management strategies to prevent the development and progression of microvascular complications in type 2 diabetes patients.Clinical trial registrationhttp://www.chictr.org.cn/, identifier ChiCTR-TRC-13003222.